Design for safety (DfS) practice in construction engineering and management research: A review of current trends and future directions. (15th July 2022) - Che Ibrahim, Che Khairil Izam; Manu, Patrick; Belayutham, Sheila; Mahamadu, Abdul-Majeed; Antwi-Afari, Maxwell Fordjour
Abstract: For past decades, design for safety (DfS) has gained growing interest among scholars and practitioners in different geographical contexts as one of the innovative practices integrating worker health and safety in the front-end of the project lifecycle. However, a systematic scientometric study appraising the research development in DfS practice in construction domain remains elusive. This paper aims to bridge this gap by conducting a scientometric review of the available DfS literature in the construction domain. A total of 167 relevant articles were retrieved using a systematic data acquisition approach from Scopus and snowballing and then put forward into a scientometric analysis to construct science maps. The scientometric review identifies the most prolific journals, authorship, cooccurrence network of keywords, article citations, and regions. An in-depth qualitative discussion is presented to provide deeper insights into the existing studies and opportunities for future research in five main DfS research themes as follows: (1) DfS concept and management; (2) DfS technological advancement; (3) DfS capability and competency; (4) DfS education; and (5) DfS sustainability. The value and uniqueness of this review study lie in its novel contribution to the body of DfS knowledge through synthesizing the wider DfS literature landscape in the construction domain. The findings offer a point of reference for both academia and industry in bridging the deficiencies in the current research and providing pathways for future directions in DfS research. Highlights: Design for safety (DfS) is a growing area of research and practice in construction. A scientometric review of DfS literature in construction is conducted. The review reveals mapping of the DfS literature from multiple perspectives. Insights into existing DfS studies and opportunities for future research are presented.